Key concepts in sport management - Byers, Terri; Slack, Trevor, 1948-; Parent, Milena M.; Sage eBooks (Los Angeles, [Calif.] ; London : SAGE, 2012)
Sharp, clear and relevant this book meets the needs of those studying and researching within the growing discipline of sport management. The intelligently cross-referenced entries provide a concise overview of the key concepts in the field guiding you through the important debates, sources and research methods in the management of sport.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Sports administration; Electronic books